Hypercholesterolemia is associated with the Apolipoprotein C-III (APOC3) genotype in children receiving HAART: An eight-year retrospective study - Rocco, Carlos Alberto (2012)
Polymorphisms in apolipoprotein genes have shown to be predictors of plasma lipid levels in adult cohorts receiving highly active antiretroviral therapy (HAART). Our objective was to confirm the association between the APOC3 genotype and plasma lipid levels in an HIV-1-infected pediatric cohort exposed to HAART. A total of 130 HIV-1-infected children/adolescents that attended a reference center in Argentina were selected for an 8-year longitudinal study with retrospective data collection. Longitudinal measurements of plasma triglycerides, total cholesterol, HDL-C and LDL-C were analyzed under linear or generalized linear mixed models. The contribution of the APOC3 genotype at sites -482, -455 and 3238 to plasma lipid levels prediction was tested after adjusting for potential confounders. Four major APOC3 haplotypes were observed for sites -482/-455/3238, with estimated frequencies of 0.60 (C/T/C), 0.14 (T/C/C), 0.11 (C/C/C), and 0.11 (T/C/G). The APOC3 genotype showed a significant effect only for the prediction of total cholesterol levels (p<0.0001). However, the magnitude of the differences observed was dependent on the drug combination (p = 0.0007) and the drug exposure duration at the time of the plasma lipid measurement (p = 0.0002). A lower risk of hypercholesterolemia was predicted for double and triple heterozygous individuals, mainly at the first few months after the initiation of Ritonavir-boosted protease inhibitor-based regimens. We report for the first time a significant contribution of the genotype to total cholesterol levels in a pediatric cohort under HAART. The genetic determination of APOC3 might have an impact on a large portion of HIV-1-infected children at the time of choosing the treatment regimens or on the counter-measures against the adverse effects of drugs.